Pre-Eruptive Magma Configurations and Petrogenetic Relationships of the Rattlesnake Tuff, Oregon–Insights From Spectacularly Banded High-Silica Rhyolite Pumices - Swenton, Vanessa M.; Streck, Martin J. (Frontiers in Earth Science, 2022)
The 7.1 Ma Rattlesnake Tuff (RST) of eastern Oregon is a widespread and voluminous (>300 km3) ignimbrite composed of 99% crystal poor (≤1%) high-silica rhyolite (HSR) and <1% dacites. Basaltic andesitic to basaltic inclusions within dacites are samples of underpinned mafic magmas. The RST HSR is comprised of five increasingly evolved compositional Groups (E–A), and HSR pumices range from white to dark grey, often co-mingled in spectacular banded pumices. Previously, Groups were interpreted as rhyolites generated by crystal fractionation within a single reservoir, where more evolved rhyolite melts formed from relatively less evolved rhyolite parents. To reassess compositional HSR Groups and their implications for tapping a single or multiple rhyolite reservoirs as well as reevaluating the petrological relationships among groups, we focus on large banded pumices for geochemical analysis. Statistical analysis of existing and new data verified these five compositional Groups and gaps, best characterized by variations in Ba, Eu/Eu*, Eu, FeO*, Hf, and Zr. Wet-liquidus temperatures, storage temperatures, and storage pressures calculated for all HSR Groups indicate similar pre-eruptive conditions (∼6.1–7.5 km depth; storage temperatures of ∼805–895°C). Differentiation trends, trends in storage pressure and temperature, and lack of crystal-rich tuff or country rock corroborate existing models for HSRs that involve a single, density-stratified magma reservoir prior eruption. Density differences are sufficient to prevent convection between layers of HSRs in a single reservoir when water content increases from 2–4 wt% from Groups E–A. However, if HSRs do not represent a liquid line, it is possible to generate HSRs through batch melting of various regional country rock. Yet, HSRs would still accumulate within the same storage zone, where density variations kept HSRs from mixing until eruption when these banded pumices formed. In either scenario, our study underscores the significance of water content and density variations for accumulating rhyolite magmas in a contiguous magma body without mixing. This has implications for other compositionally heterogenous rhyolitic ignimbrites where natural samples do not provide comparable evidence to argue for pre-eruptive confocal storage of different rhyolite magmas as is the case for the Rattlesnake Tuff.